AVALIAÇÃO DO EFEITO DE INSETICIDAS SOBRE A JOANINHA HIPPODAMI. CONVERGENS GUÉRIN-MENEVILLE (COLEOPTERA: COCCINELLIDAE) EM ALGODOEIRO - Scarpellini, J.r.; Andrade, D.j. De [UNESP] (Instituto Biológico, 2020)
The combination of chemical and biological methods to control pests is essential to ensure the sustainability of agricultural system, to reduce using of chemicals products. The objective this work was to evaluate the effects of insecticides on the coccinellid predatory Hyppodamia convergens, the cotton plant, in conditions laboratory and field. Were the following treatments established, expressed in g or mL of active ingredient of insecticide per hectare: flonicamid to 50, 80 and 150 g, thiamethoxam at 200 g to 150 g acetamiprid, imidacloprid to 250 mL and control without application. The evaluation effect of insecticides applied directly and indirectly (residual effects on leaves) on H. convergens, was performed by quantification of insects survived to 7 days after application. Based on the results of experiments, we can conclude that among the insecticides evaluated, flonicamid caused the lower mortality of H. convergens. The insecticides thiamethoxam, acetamiprid and imidacloprid showed similar behavior, causing high mortality of H. convergens.

A associação dos métodos químico e biológico no controle de pragas é fundamental na sustentabilidade do sistema agrícola, auxiliando a redução de químicos derivados de petróleo. O objetivo do trabalho foi avaliar o efeito de inseticidas sobre o coccinelídeo predador Hippodamia convergens, na cultura do algodoeiro, em condições de laboratório e de campo. Foram estabelecidos os seguintes tratamentos, expressos em g ou mL de p.c. do inseticida por hectare: flonicamida a 50, 80 e 150 g, tiametoxam a 200 g, acetamiprido a 150 g, imidacloprido a 250 mL e testemunha sem aplicação. A avaliação do efeito dos inseticidas aplicados diretamente e indiretamente (efeito de contato em resíduo seco do inseticida) sobre H. convergens, foi realizada por meio da quantificação de insetos sobreviventes após a aplicação. Com base nos resultados dos experimentos, pode-se concluir que dentre os inseticidas avaliados, flonicamida ocasionou a menor mortalidade de H. convergens. Os inseticidas tiametoxam, acetamiprido e imidacloprido apresentaram comportamento semelhante, acarretando alta mortalidade de H. convergens.
EVALUATION OF THE EFFECT OF INSECTICIDES ON LADY BEETLES HIPPODAMIA CONVERGENS GUÉRIN-MENEVILLE (COLEOPTERA: COCCINELLIDAE) IN COTTON PLANT
Keywords: Selectivity; Gossypium hirsutum; biological control; natural enemy; Seletividade; Gossypium hirsutum; controle biológico; inimigo natural